2022
DOI: 10.1007/s43076-022-00215-1
|View full text |Cite
|
Sign up to set email alerts
|

Can Character Strengths Predict College Adjustment? A Study Carried Out in Nursing Students in the Argentine Republic

Abstract: The objective of the study was to analyse and develop an explanatory model of the relationship between strengths of character and adaptation to the university in nursing students from different educational institutes of the Provinces of Buenos Aires and Formosa, in its three dimensions—academic, social, and institutional. The prediction model was based on the 24 character strengths of 210 nursing students from different educational institutes of the Provinces of Buenos Aires and Formosa, aged between 20 and 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
1
1
0
1
Order By: Relevance
“…The Hypothesis 1 was confirmed. This partially agrees with earlier research findings [ 45 , 46 ]. The career construction theory believes that career development is a dynamic process full of internal motivation.…”
Section: Discussionsupporting
confidence: 94%
“…The Hypothesis 1 was confirmed. This partially agrees with earlier research findings [ 45 , 46 ]. The career construction theory believes that career development is a dynamic process full of internal motivation.…”
Section: Discussionsupporting
confidence: 94%
“…La investigación previa también ha mostrado aportes interesantes en relación de las fortalezas del carácter con variables psicoeducativas (Cobo y García-Álvarez, 2023), entre ellas: ajuste y adaptación universitaria (Grinhauz et al, 2022), sentido de vida, metas personales y adaptabilidad de carrera (Lin & Jiang, 2023), personalidad resistente académica y compromiso (Arias et al, 2020). Con respecto a la salud, han sido asociadas positivamente a resiliencia (Kuang et al, 2023), salud mental y bienestar (Azañedo et al, 2020;Chan et al, 2022;De la Fuente et al, 2022), e inversamente con variables consideradas psicopatológicas, como afectos negativos y angustia psicológica (Dolev-Amit et al, 2021), ansiedad rasgo-estado (Mezo y Elhai, 2021), neuroticismo y afecto negativo (Anjum y Amjad, 2021), dificultades en el afrontamiento del estrés (Ferradás et al, 2021;Huber et al, 2017), depresión, ansiedad, conductas de riesgo y consumo de alcohol (Karris et al, 2021).…”
Section: -281unclassified
“…First, based on functional equivalence and conceptual equivalence, Duan et al [ 12 ] suggested that some items of the international measurement of virtue, values in action inventory of strengths (VIA-IS), might not be applicable in the Chinese context. Second, although subsequent studies revealed that character strengths relate positively to positive outcomes, including life satisfaction [ 13 ], well-being [ 14 ], and adaptability [ 15 ] in different contexts, there is a lack of scholarship on student virtues and resilience in Hong Kong. Third, despite the growing literature on student virtues, the potential impact of individual factors (i.e., both gender and school level) on virtue and resilience are not well understood.…”
Section: Introductionmentioning
confidence: 99%